A Critical Interpretation On Mutrashmari According To Sushruta Samhita - A Brief Review Study - Ahamad, Mohd. Akeel; Meena, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
One of the most famous Mutra vaha Srotasa (Channels of urinary system) diseases is Mutrashmari (Urinary calculi). Mutrashmari has been listed by Acharya Sushruta as one of the Ashta Mahagada, since it is not easy to treat and more attention needs to be paid to its cure. It is associated with Urolithiasis or Urinary Calculi in modern medical science. Due to different factors such as altered eating habits, modified lifestyle, stress, pressure, environmental contamination, etc., the incidences of Mutrashmari (Urinary Calculi) are rising at the present age. These variables have been classified as Nidana in Ayurvedic texts. Due to Nidana Sevana (Consumption of Etiological Factors), Doshas get aggravated, along with Dushya they induce Sroto Dushti, and then sickness manifests, Nidana (Etiological Factors), plays a major role in the incidence of disease. Both three Doshas are active in Mutrashmari’s Samprapti (Pathogenesis of Urinary Calculi), Vata, Pitta and Kapha, so knowing the Samprapti (Pathogenesis) is necessary for disease management, since Chikitsa is the disintegration of Samprapti Sanghatana (Breaking the Pathogenesis). Srotasa is an effective Samprapti Ghataka (Pathogenic factor) for disease development. Pathya is a nutrient compliant with Srotasa (Body channels). Srotasa is protected by the avoidance of causative factors of the disease and the compatibility of food with Srotasa (Body channels), which inhibits Srotovaroda (Obstructions of Body channels) and thereby prevents the disease. This paper focuses primarily on the study of Mutrashmari (Urinary Calculi) in Nidana-Samprapti (Causative factor Pathogenesis) and the role of Nidana Parivarjana (avoiding the cause) and Pathya Kalpana (Ayurvedic Dietetics) in their care.